2017
DOI: 10.1016/j.foodpol.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ preferences for supermarket contracts in Kenya

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
103
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 43 publications
13
103
3
3
Order By: Relevance
“…When E π WI C w * C = E π sc I * sc + n Θ r − k − E π F I * d , under the risk transfer mechanism, the company withdraws all profits increased from the coordination of the supply chain. Combining the formulas (2), (6), and (20), we can…”
Section: Risk Transfer Mechanism Based On Weather Index Insurancementioning
confidence: 99%
See 3 more Smart Citations
“…When E π WI C w * C = E π sc I * sc + n Θ r − k − E π F I * d , under the risk transfer mechanism, the company withdraws all profits increased from the coordination of the supply chain. Combining the formulas (2), (6), and (20), we can…”
Section: Risk Transfer Mechanism Based On Weather Index Insurancementioning
confidence: 99%
“…According to the analysis of Proposition 2, we can see that the total profit of the company and the farmer under the decentralized decision is less than the profit under the centralized decision. It shows that when the company and the farmer are maximizing their own profits, they make decisions for their own maximum benefits instead of the 6 Complexity benefit of the supply chain system, which leads to a loss of performance in the supply chain system. Therefore, it is necessary to design a reasonable mechanism to improve the farmer's optimal agricultural investment level under decentralized decision so as to ease the "double marginalization" brought about by the distorted investment level of agricultural resources, so as to ensure the stable operation of the supply chain system.…”
Section: Propositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a large theoretical literature on relational contracting and reputations, there have been few empirical studies published (see discussion in [Lafontaine and Slade, ]). We are aware of only three other articles that specifically test for the impact of contract enforcement on contract farming: a field experiment conducted in Vietnam (Saenger et al., ), a choice experiment conducted in Thailand (Schipmann and Qaim, ), and a choice experiment conducted in Kenya's supermarket fresh produce supply chain (Ochieng et al., ). Both the study in Vietnam and the study in Thailand found that lack of exogenous contract enforcement mechanisms impacted the intensive supply margins for these two markets.…”
Section: Introductionmentioning
confidence: 99%